PENGARUH BUDAYA KERJA, KOMITMEN ORGANISASI, DAN DISIPLIN TERHADAP KINERJA PERAWAT DI UPTD RUMAH SAKIT JIWA PROVINSI BALI - Ni Komang Ayu Wintari; Agus Wahyudi Salasa Gama; Ni Putu Yeni Astiti (EMAS, 2021)
Public demand for quality health services is a challenge for health service providers, one of which is hospitals. Patient satisfaction is an indicator of service that is influenced by the performance of nurses because nursing personnel are the first and longest contacts with patients, so that they can represent the entire image and appearance of the hospital. This study aims to determine the effect of work culture, organizational commitment and work discipline on the performance of nurses at the Mental Hospital in Bali Province. The population in this study were all 104 executing nurses who worked in the inpatient room of the Bali Province Mental Hospital, which were selected by accidental sampling. The analytical tool used to test the hypothesis is multiple regression. The results showed that work culture had a positive and significant effect on nurse performance. Organizational commitment has a positive and significant effect on nurse performance. Work discipline has a positive and significant effect on nurse performance. Mental Hospital Management in Bali Province can improve communication, monitor and evaluate by carrying out regular and scheduled supervision